Chemical Composition and Biological Activities of Essential Oil from Citrus aurantiifolia Peel Waste for Use in Aromatherapy Products - Itsarasook, Khwunjit; Chantree, Kanlayaporn; Prompamorn, Piyanuch; Modsuwan, Surapha; Tanghiranrat, Jittarawadee; Srisukong, Amornrat; Wutisatwongkul, Jantharat (Journal of Food Health and Bioenvironmental Science, 2025)
The processing of lime (Citrus aurantiifolia (Christm.) Swingle) results in considerable waste, including peels, seeds, and pomace. D-limonene belongs to the category of monoterpenoids, and it is one of the chemicals composed within lime oil. This study aims to explore the antioxidant and anti-inflammatory properties of essential oil extracted from lime peel waste to enhance its market value, with potential uses in natural fragrances for skin cosmetics and SPA products. Essential oils were extracted from lime peels using hydro distillation, and their properties were evaluated. Chemical profiling by gas chromatography-mass spectrometry (GC-MS) revealed D-limonene (51.45%) as the dominant compound among eleven identified constituents. The lime peel oil was found to be non-cytotoxic to normal human dermal fibroblast (NHDF) cells. Additionally, it demonstrated significant in vitro antioxidant activity, as shown by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay and the reduction power measured through free radical scavenging activity (FRAP) tests. The essential oil also exhibited inhibitory effects against several skin pathogens, including Escherichia coli (ATCC 8739), Pseudomonas aeruginosa (ATCC 9027), Staphylococcus aureus (ATCC 6538), and Candida albicans (ATCC 10231). Significantly, the lime peel oil exhibited a concentrationdependent inhibition of nitric oxide production, with the 25 µg/mL concentration showing a greater reduction in nitric oxide levels compared to the other concentrations when assessed against the lipopolysaccharide-treated group. A massage oil formulation containing lime peel oil was created, demonstrating favorable physicochemical properties and stability at room temperature for 30 d. Overall, these results indicate that lime peel oil, sourced from waste, holds promising potential as a natural fragrance in skin cosmetic and SPA products, in addition to possessing significant antioxidant properties.